Ut omnia sint ordinatissima. On the Relation between Order and Eternal Law in Augustine (Doctor Virtualis, 2024)
The article examines the function of the reference to order in the two definitions of the eternal law proposed by Augustine in Book I of De libero arbitrio and Book XXII of Contra Faustum Manichaeum. The first definition posits the highest degree of order in everything as just, while the second posits the preservation of the natural order as obligatory and its disruption as forbidden. Although not identical, the two definitions are consistent and agree in attributing to the concept of order a regulatory role in the legal and moral spheres, which does not crystallise the existing, particular norms but, on the contrary, urges their adaptation to the variability of actual situations.
Keywords: Augustine; law; order